Semiconductor modeling techniques - Xavier, Marie; Balkan, Naci (Springer Series in Materials Science, 2012)
This book describes the key theoretical techniques for semiconductor research to quantitatively calculate and simulate the properties. It presents particular techniques to study novel semiconductor materials, such as 2D heterostructures, quantum wires, quantum dots and nitrogen containing III-V alloys. The book is aimed primarily at newcomers working in the field of semiconductor physics to give guidance in theory and experiment. The theoretical techniques for electronic and optoelectronic devices are explained in detail.